2010
DOI: 10.3109/13561820903130149
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a primary healthcare pharmacist

Abstract: Pharmacists have been encouraged to enhance their role on primary healthcare teams; but, the profession has yet to be involved to the degree in which a substantial impact can be made. The objective of this study was to provide guidance on how to integrate a pharmacist into an already established primary healthcare team. Using action research, a panel of established primary healthcare pharmacists identified clinical activities for a primary healthcare pharmacist tailored for the project site. The results were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 10 publications
1
38
1
1
Order By: Relevance
“…The studies were from 11 countries and most of the studies were conducted in Canada ( n = 17) [45, 5153, 55, 57, 63, 65, 66, 71, 7880, 82–84, 87], followed by the USA ( n = 12) [40, 43, 44, 47, 49, 56, 58, 72, 76, 77, 85, 86], the UK ( n = 7) [39, 48, 59, 64, 68, 70, 81], Australia ( n = 4) [42, 73–75], New Zealand ( n = 2) [41, 62], Sweden ( n = 2) [54, 67], France ( n = 1) [50], Spain ( n = 1) [46], Netherlands ( n = 1) [60], Brazil ( n = 1) [61] and Republic of South Africa ( n = 1) [69]. Thirty-two different primary care professionals participated in these studies, with most of the data relating to General Practitioners/Family Physicians (42 papers), nurses (35 papers), pharmacists (14 papers) and administrative staff (11 papers) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were from 11 countries and most of the studies were conducted in Canada ( n = 17) [45, 5153, 55, 57, 63, 65, 66, 71, 7880, 82–84, 87], followed by the USA ( n = 12) [40, 43, 44, 47, 49, 56, 58, 72, 76, 77, 85, 86], the UK ( n = 7) [39, 48, 59, 64, 68, 70, 81], Australia ( n = 4) [42, 73–75], New Zealand ( n = 2) [41, 62], Sweden ( n = 2) [54, 67], France ( n = 1) [50], Spain ( n = 1) [46], Netherlands ( n = 1) [60], Brazil ( n = 1) [61] and Republic of South Africa ( n = 1) [69]. Thirty-two different primary care professionals participated in these studies, with most of the data relating to General Practitioners/Family Physicians (42 papers), nurses (35 papers), pharmacists (14 papers) and administrative staff (11 papers) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen papers were based on co-located teams [43, 48, 49, 53, 54, 56, 58, 65, 70, 71, 75, 8385, 87] and 16 were from settings where the team is made up of some co-located professionals who are working with others in different sites [40, 42, 45, 46, 60, 64, 66, 68, 69, 73, 74, 80–82, 86]. Details about the physical infrastructure of the team being studied were not explicit in 18 papers [39, 41, 44, 47, 5052, 55, 57, 61–63, 67, 72, 7679].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study support the findings of previous studies on general practitioners and community pharmacists. Interactional and practitioner determinants such as, open communication, trust, respect, a willingness to work together, past professional experiences, mutual recognition of roles and expectations have been reported in previous studies (Bradley et al, 2008;Dieleman et al, 2004;Kolodziejak, 2010;Liu, Doucette, & Farris, 2010;Makowsky et al, 2009;McGrath et al, 2010;Snyder et al, 2010;Zillich, McDonough, Carter, & Doucette, 2004). For example, a US survey of 340 primary care physicians found that participant, context and exchange characteristics influenced collaborative relationships with exchange characteristics such as role specification, trustworthiness and relationship initiation the most influential drivers (Zillich et al, 2004).…”
Section: Discussionmentioning
confidence: 79%
“…A simple protocol should be developed that is similar to existing team procedures for referring patients to other consultants. 25,27,[34][35][36] It may be useful to create a pharmacist referral form to facilitate the process (samples available at www.impactteam.info). Access to administrative support for booking patient appointments or sending faxes is also very useful and will ensure efficient use of pharmacist time.…”
Section: Practiceguidelinesmentioning
confidence: 99%